Perspective of 2D Integrated Electronic Circuits: Scientific Pipe Dream or Disruptive Technology?. Issue 48 (10th April 2022) - Waltl, Michael; Knobloch, Theresia; Tselios, Konstantinos; Filipovic, Lado; Stampfer, Bernhard; Hernandez, Yoanlys; Waldhör, Dominic; Illarionov, Yury; Kaczer, Ben; Grasser, Tibor
Abstract: Within the last decade, considerable efforts have been devoted to fabricating transistors utilizing 2D semiconductors. Also, small circuits consisting of a few transistors have been demonstrated, including inverters, ring oscillators, and static random access memory cells. However, for industrial applications, both time‐zero and time‐dependent variability in the performance of the transistors appear critical. While time‐zero variability is primarily related to immature processing, time‐dependent drifts are dominated by charge trapping at defects located at the channel/insulator interface and in the insulator itself, which can substantially degrade the stability of circuits. At the current state of the art, 2D transistors typically exhibit a few orders of magnitude higher trap densities than silicon devices, which considerably increases their time‐dependent variability, resulting in stability and yield issues. Here, the stability of currently available 2D electronics is carefully evaluated using circuit simulations to determine the impact of transistor‐related issues on the overall circuit performance. The results suggest that while the performance parameters of transistors based on certain material combinations are already getting close to being competitive with Si technologies, a reduction in variability and defect densities is required. Overall, the criteria for parameter variability serve as guidance for evaluating the future development of 2D technologies. Abstract : 2D field‐effect‐transistors (FETs) are affected by time‐dependent changes in their performance, which must be minimized for industrial‐scale applications. In this work, the stability of circuits based on 2D transistors is evaluated. The results suggest that the performance parameters of certain material combinations for 2D FETs are already close to Si technologies. Furthermore, parameter variability criteria are formulated to evaluate the future development of 2D technologies.